The Effect of Eating Patterns on the Learning Achievement of Grade X DKV Students at SMK Budi Bakti Ciwidey - Sari, Fitri Puspita; Elhany, Al-Ainna Rossel Ekasuci (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Academic success is a measure of educational progress that is shaped by multiple factors, one of which is nutrition. A poor diet can interfere with cognitive abilities and may adversely impact the academic performance of teenagers. This research aims to explore the link between eating habits and the academic performance of 10th-grade students in Visual Communication Design (DKV) at SMK Budi Bakti Ciwidey, located in Bandung Regency. A quantitative research method with a cross-sectional layout was employed for the study. The sample included 58 students chosen through simple random sampling from a total of 135 students. Data on dietary habits were gathered using a Food Frequency Questionnaire (FFQ), while academic performance information was collected from report card grades for the odd semester of the 2024/2025 academic year. Data analysis was performed univariately and bivariately utilizing Fisher's Exact Test at a significance level of 5%. Findings indicated that 74.1% of participants maintained a nutritious diet, and 96.6% exhibited commendable academic performance. The bivariate test results revealed no significant correlation between dietary habits and academic achievement (p = 0.064). The study concluded that dietary habits were not meaningfully connected to academic achievement among students in this case. It appears that academic performance is more impacted by other elements such as motivation to learn, support from family, and the educational environment. However, maintaining a healthy diet continues to be essential for fostering the health and cognitive abilities of adolescents.